Laser-generated Cu plasma in vacuum and in nitrogen gas. (August 2020) - Torrisi, L.; Cutroneo, M.; Torrisi, A.
Abstract: A pulsed ns IR laser at about 10 10  W/cm 2 intensity is employed to irradiate a Cu target placed in a vacuum and in nitrogen gas. The produced plasma is characterized in terms of emitted ions and photons as a function of the nitrogen pressure in the chamber. The mechanisms of ion gas interactions are investigated in terms of Cu ion energy loss and X-ray attenuation using an ion collector and a SiC detector. A fast CCD camera in the visible region has produced the collision images of the ions with the nitrogen molecules. A plasma temperature of about 44 eV, an emission of soft X-rays up to about 100 eV, an ablation yield of about 2.4 × 10 15 atoms/pulse, a maximum Cu ion acceleration of 1.4 keV and a maximum ionization up to Cu 9+ were measured in high vacuum. Highlights: A Cu plasma produced by pulsed laser at 10 10  W/cm 2 intensity in high vacuum is characterized. The presence of nitrogen gas reduces the Cu ion energy. The presence of nitrogen gas reduces the intensity of Cu X-ray emission. The interaction of Cu ions with nitrogen molecules produces visible light. The plasma plume interacting with nitrogen gas at different pressures is photographed.